(untitled) (Journal of Environmental Science and Natural Resources, 2017)
An experiment was conducted to evaluate the efficacy of nine botanical extracts on plant growth, yield and pest management in eggplant field. Aqueous extracts of dried leaves of Nicotiana tabacum, Aegle marmelos, Ficus hispida, Lawsonia inermis, Vitex negundo and seeds of Carum roxburghianum, Corchorus capsularis and Swietenia macrophylla and bulb of Allium sativum were prepared and sprayed in experimental eggplant field at University of Rajshahi during January 1, 2014 to May 5, 2014. Out of these nine botanicals, Nicotiana tabacum extract showed best performance against pest attack in eggplant field. The leaf extract of Ficus hispida also showed good efficacy in the protection of eggplant from pest attack. The highest plant length and fruit yield were recorded in the treatment of Nicotiana tabacum, whereas second and third highest productions were observed in Aegle marmelos and Ficus hispida treatments, respectively. Both Allium sativum and Carum roxburghianum extracts were found to show phyto-toxicity to eggplant and hampered the plant growth and yield. J. Environ. Sci. & Natural Resources, 10(1): 137-140 2017